Innovation and Entrepreneurship: Theory, Policy and Practice - Carayannis, Elias G (Springer, 2015)
This book aims to meet the needs of education and training in modern techniques of innovation and entrepreneurship, and focuses on the detailed presentation of successful business practices. As today's global economic landscape is changing rapidly, the ability of businesses to introduce new products and services to the market faster than their competitors is perhaps their most distinct competitive advantage. This becomes obvious by the significant market share that the most innovative companies gain while increasing profitability. Extensive research in this field has demonstrated that companies that are constantly innovating normally double their profits compared to others. Moreover, establishing successful practices and policies of innovation management, through which ideas evolve from conception through evaluation to implementation and commercialization, become the basis for economic growth at the firm, industry, national, regional, and global levels.